2022
DOI: 10.3390/ijms23094745
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Material Characteristics of MoS2/Cu2O Sensor for Detection of Lung Cancer Cell Types in Hydroplegia

Abstract: In this study, n-type MoS2 monolayer flakes are grown through chemical vapor deposition (CVD), and a p-type Cu2O thin film is grown via electrochemical deposition. The crystal structure of the grown MoS2 flakes is analyzed through transmission electron microscopy. The monolayer structure of the MoS2 flakes is verified with Raman spectroscopy, multiphoton excitation microscopy, atomic force microscopy, and photoluminescence (PL) measurements. After the preliminary processing of the grown MoS2 flakes, the sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 76 publications
0
18
0
Order By: Relevance
“…Barbeiro et al (2019) used NBI to study gastrointestinal endoscopy and found that NBI can be used as an important auxiliary image for WLI, which can improve the detection of gastrointestinal lesions. Apart from CAD, many biosensors have been recently researched to detect different cancer types [ 35 , 36 , 37 ]. However, most of these biosensors have a high limit of detection, thereby leading to poor sensitivity in early-stage cancer detection.…”
Section: Introductionmentioning
confidence: 99%
“…Barbeiro et al (2019) used NBI to study gastrointestinal endoscopy and found that NBI can be used as an important auxiliary image for WLI, which can improve the detection of gastrointestinal lesions. Apart from CAD, many biosensors have been recently researched to detect different cancer types [ 35 , 36 , 37 ]. However, most of these biosensors have a high limit of detection, thereby leading to poor sensitivity in early-stage cancer detection.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, detecting esophageal cancer in its early stage is vital to increasing the five-year survival rate. One of the methods of detecting esophageal cancer is through a biosensor; however, most biosensors cannot detect cancer at the early stages [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…One way to detect cancer during its early stages is by using a cancer biosensor [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The specificity, quickness, compactness, and price of a biosensor present prospects for regionalized medical diagnoses [ 29 ].…”
Section: Introductionmentioning
confidence: 99%